Hypersensitivity Reaction to Orthopedic Implants: Current State of the Problem (Literature Review) - Lazarenko, H.O.; Boiko, I.V. (TERRA ORTHOPAEDICA, 2022)
Summary. Metal hypersensitivity reaction (MHR) is one of the most controversial and complex issues in orthopedic and traumatological practice. An analysis of the English-language literature was carried out in order to determine the current state of the problem in the diagnosis, verification and treatment tactics of patients with a hypersensitivity reaction to orthopedic implants. It was determined that at the moment there is no universal algorithm for the diagnosis and treatment of this pathology in the world. Currently, the most common diagnostic methods are patch testing and the lymphocyte transformation test, which assess a response, but there is no clear consensus on how these tests should be used in the clinical setting. In the given analysis, the issue of diagnosis and treatment was considered in more detail.